Mixed methods quality evaluation of structured interprofessional medical ward rounds. Issue 2 (9th February 2020) - Redley, Bernice; Campbell, Don; Stockman, Keith; Barnes, Sara
Abstract: Background: Standardised structure and content of interdisciplinary medical ward rounds can promote patient safety and patient‐centred teamwork. Aims: To evaluate interdisciplinary ward rounds using a Structured Interdisciplinary Bedside Rounding (SIBR) intervention. Methods: The study involved multi‐method, repeat measures with a non‐equivalent control group. Non‐participant observations were collected at: 1 and 6 months, on an intervention ward that introduced SIBR; and a control ward that continued traditional rounds. Focus group and survey data were also collected on the intervention ward. Participants were clinicians (medicine, nursing and allied health) working in two general medicine wards at a tertiary hospital in Melbourne, Australia. Results: Seventy‐eight patient rounds were observed at Time 1, and 239 at Time 2. The SIBR ward rounds had all clinician disciplines represented, whereas allied health and nurses were present for less than 20% of non‐SIBR rounds. Interdisciplinary participation and frequency of desired clinician behaviours increased, and variability in duration of time per patient decreased, on the SIBR rounds. Longitudinal data reflected decreased performance of some SIBR behaviours in the intervention ward, while some desired behaviours increased in the control ward. Qualitative survey and focus group data indicated many positive views, but fit with broader ward routines impacted SIBR implementation. Conclusions: The overall recommendation by staff was that SIBR should continue. The results provide insights into the adoption of SIBR behaviours and illustrated diffusion of behaviours across wards. Highlighting successes and identifying barriers can help meet challenges for ongoing improvement.